Design, Implementation and Testing of a Network-Based Earthquake Early Warning System in Greece - Bracale, M.; Colombelli, S.; Elia, L.; Karakostas, V.; Zollo, A. (Frontiers in Earth Science, 2021)
In this study we implemented and tested the Earthquake Early Warning system PRESTo on the Greek Ionian islands of Lekfada, Zakinthos and Kefalonia. PRESTo (PRobabilistic and Evolutionary early warning SysTem, Satriano et al., 2010), is a free and open source platform for regional EEW developed by the RISSC-Lab research group at the University of Naples Federico II, which is currently under experimentation in the area covered by the Irpinia Seismic Network (ISNet). The three Ionian islands selected for this study are located on the North-Western part of the Hellenic trench. Here the seismicity rate and the seismic risk are among the highest in Europe and this makes the application of EEWS systems extremely important to mitigate the potential damage caused by earthquakes. Here we studied the feasibility of implementing an EWS on an existing seismic network, which was not specifically made for earthquake early warning purposes, and evaluated the performance of the system, using a data set of real-earthquake recordings. We first describe the technical details of the implementation of PRESTo in the area of interest, including the preliminary parameter configuration and the empirical scaling relationship calibration. Then we evaluated the performance of the system through the off-line analysis of a database of real earthquake records belonging to the most recent M > 4.0 earthquakes occurred in the area. We evaluated the performance in terms of source parameter estimation (location, magnitude), accuracy of ground shaking prediction and lead-time analysis. Finally, we show the preliminary results of the real-time application of PRESTo, performed during the period 01-31 July 2019.